Samras in Gram Panchayats of Gujarat: Undermining Democracy by Means of Consensus? - Bandi, Madhusudan (Journal of Rural Development, 2024)
Among the 10,118 Gram Panchayats (GP) in Gujarat that were going to general/mid-term elections and by-elections, 1,267 were declared ‘samras gams (villages)’ on December 7, 2021, the last day of withdrawal of nomination. Samras gams are those villages where a sarpanch and all the ward members are chosen by consensus by not going to polls. They become eligible to receive monetary benefits for the development works. If the choice of the people in the elections held in two decades since the inception of the scheme is observed, it suggests that just about 20 per cent of the GPs prefer samras. The major criticism of the concept has been that government-backed financial incentives undermine the concept of free and fair elections. Besides, it is found that the elites who have a grip on the village economy in the respective GP constituencies decide to go for samras, which indirectly results in the denial of political rights to the socio-economically weaker section of people. The political parties may have introduced the scheme with the best of intentions to halt the regular reporting of violence erupting after the elections in the villages and affecting the development process in the GPs. However, after weighing the merits and demerits of the scheme on the ground, scrapping it altogether appears to be an ideal move to continue with the democratic spirit at the local level of governance.